EMPOWERING LOCAL COMMUNITIES IN DEVELOPMENT IN TISTA TOURISM VILLAGE, KERAMBITAN DISTRICT, TABANAN REGENCY - Adnyani, Ni Made Ina; Bendesa, I Komang Gde (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
Community-based tourism is supported by ownership, management and participation of community members in tourism activities. CBT is a development that involves local people who are directly involved or who are not directly involved in the tourism industry. This study aims to (1) analyze the involvement of community empowerment of CBT in Tista Tourism Village, (2) analyze the empowerment of local communities and CBT towards the welfare of the community in Tista Tourism Village, and (3) analyze CBT mediating the relationship between empowering local communities in community welfare Tista Tourism Village. The analysis technique used is path analysis technique. The results of the study show that (1) positive community empowerment of CBT, (2) CBT has a positive effect on Community Welfare, and (3) CBT mediates the relationship between community empowerment and community welfare. The lack of information to access tourist sites is the duty of stakeholders in Tista Tourism Village, with the control of tourism communities will get more benefits not only for local communities but also for the community. Therefore, the presence of tourism communities will be able to create employment opportunities, reduce poverty and bring a positive impact on environmental conservation can also increase tourism .